STUDY OF LITERATURE ON VARIATION IN THE APPLICATION OF THE NUMBERED HEAD TOGETHER TYPE OF COOPERATIVE LEARNING MODEL AND ITS EFFECT ON STUDENTS’ LEARNING COMPETENCIES - Helka Yuliati; Relsas Yogica; Zulyusri Zulyusri; Yusni Atifah (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The purpose of writing this article is to see the variation in the application of the cooperative learning model type Numbered Head Together and its effect on the learning competence of students. This type of research is a literature study through review articles that refer to previous research. The data used is secondary data, namely a collection of articles that have been SINTA accredited and related to the cooperative learning model Numbered Head Together. Based on the literature review, it was found that the application of the cooperative learning model type Numbered Head Together can improve the learning competence of students in aspects of knowledge, aspects of attitudes, and aspects of skills.